MIRRORED PATHS: ANALYSING GABI BRAUN AS EREN JAEGER’S GENDERED REFLECTION IN ATTACK ON TITAN. - Nandakumaran, Aswathynanda; Pai, Geeta R. (International Journal of Research -GRANTHAALAYAH, 2025)
Attack on Titan, a Japanese manga and anime series by Hajime Isayama, depicts a dystopian world where humanity battles man-eating giants known as Titans. While the show revolves, initially, around three pre-teens, particularly Eren Jaeger as the central protagonist, the plot progresses to explore darker themes of trauma, war, the conflict between humanity and individualism, and genocide. This paper explores Gabi Braun as the gendered reflection of Eren Jaeger, focusing on their similar character arcs and eventual ideological transformations. Introduced halfway through the show from an opposing perspective, Gabi shares significant parallels with Eren, going through deep-seated personal trauma through violence that eventually becomes a catalyst for their characteristic evolution, which begins and ends in opposing values. The analysis intends to examine how Gabi’s complicated youth and gender act as Eren’s narrative counterpart. Eren indirectly represents a hyper-masculine personification of hatred and blind vengeance. Defying norms and challenging traditional gendered representations, Gabi embodies unrelenting steadfastness and aggression not typically ascribed to female fictional characters. Utilising Judith Butler’s Gender Performativity and Sigmund Freud’s concept of Thanatos (Death Drive), this study explores and critiques both these characters’ mirrored journey from naivety to hatred or the realisation of futility in revenge. The paper highlights Gabi’s indirect portrayal as a vessel to critique Eren’s transformation to bargain for absolute freedom at the cost of his moral consciousness. This comparison provides a nuanced perspective into their characters and a commentary on the dehumanising effects of ideological fanaticism and the possibilities of redemption beyond the cycle of hate.